Social Media Use for Decision Making During Politics in a Multicultural Society: a Case Study of Nigeria - Shem, Woyopwa; Gambo, Sarah; Graham Abel, Billy (The Journal of Society and Media, 2023)
This study explored the use of social media for decision-making during politics in a multicultural society. The study was anchored on the public sphere theory and was guided by three research objectives, which are to probe the role of social media in building an inclusive society, investigate the role of social media in making an informed citizenry that deepens democracy, and identify the challenges that confront the practice of social media in a multicultural society. The study adopted a qualitative approach where secondary data from extant empirical studies were collated, presented, and analyzed. The study's findings revealed that using social media platforms is a veritable tool to adopt during politics and that these platforms influence citizens' political decisions. However, the study's findings also revealed that social media faces challenges during politicking, especially in a multicultural society like Nigeria. Some of the identified challenges include the proliferation of misinformation, fake news, and hate speech, among other forms of practices that are damaging to a multicultural and democratic society. The paper, therefore, recommends, among other things, that there is a swift need for stakeholders and other relevant government agencies to educate netizens on the dangers of using social media adversely during politics